Eventide - Haruf, Kent (Random House Audio, 2004)
In a small town where people encounter each other frequently, destinies entwine easily--and surprisingly. The McPherson brothers see the single mother they'd taken in move away to college; a young boy living alone with his grandfather helps a neighbor whose husband has left her alone to raise their daughters; a child of a disabled couple suffers indignities at school ... A novel about survival, resilience, and, ultimately, hope's triumph over despair.